On-the-job learning and earnings: Comparative evidence from Morocco and Senegal - Christophe Jalil Nordman; François-Charles Wolff (Institute for the Study of Labor (IZA), 2012)
In this paper, we consider a model of on-the-job learning where workers learn informally by watching and imitating colleagues. We estimate the rate of knowledge diffusion inside the firm using two matched worker-firm data sets from Morocco and Senegal. We rely on non-linear least squares to estimate the structural parameters of the informal learning model and account for firm heterogeneity using firm factors derived from a principal component analysis. We find that the rate of knowledge diffusion is around 7 percent in Morocco and Senegal, but part of the learning-by-watching returns stems from firm heterogeneity. Informal training significantly affects the shape of returns to tenure in these two countries. Finally, we estimate an extended model with both learning-by-watching and learning-by-doing and find significant benefits from imitating colleagues in Morocco.
Keywords: J24; J31; O12; 330; earnings functions; informal training; learning-by-watching; learning-by-doing; returns to tenure; Morocco; Senegal; Betriebliches Bildungsmanagement; Learning by Doing; Wissenstransfer; Bildungsertrag; Betriebszugehörigkeit; Marokko; Senegal